ANALISIS TRANSPARANSI PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA DESA (STUDI KASUS PADA DESA SAHRAEN KECAMATAN AMARASI SELATAN KABUPATEN KUPANG - Martina Kaisriani Rupa (JAKA - Jurnal Jurusan Akuntasi, 2022)
This research on transparency of village revenue and expenditure budget management (APBDes) aims to determine the transparency process of village revenue and expenditure budget management especially at the budgeting, implementation and accountability stages. This type of research uses a qualitative description. Data collection was carried out by means of questionnaires, interviews and documentation which will be analyzed using qualitative descriptive methods in three stages that is data reduction, data presentation, verification and conclusion. The result of this indicate that in general, village financial management in Saharen Village has been implemented well. But there are some problems that happen including the transparent stage of management on village income and expenditure budget for the last 4 years, the village apparatus work using the application so the community such as a RT/RW are not directly involved in the management of the APBDes, the planning stage of the village is lately submitting by secretary and it means over time to collect into local government. And the accountability stage of the village apparatus submitting accountability reports to the community by attaching billboards but not in detail so that the village of sahraen has not been said to transparent or open to the wider community.